Preparation and Characterization of Cellulose/Montmorillonite Hybrid Membranes - Moulahcene-Abdelli, Fethia; Aliouche, Djamel (Journal of Composites and Biodegradable Polymers, 2015)
The compounding of cellulose and inorganic Montmorillonite (MMT) on microscale molecular level has high potential to greatly improve the thermal stability, decay resistance and other properties of cellulose fibres. Pristine Algerian MMT was first sodium modified as Na-MMT, then organically modified as organophilic OMMT by using Octadecylamine. With OMMT and fibrous cellulose from waste cotton, cellulose/MMT composites were prepared via incorporation from solution process and characterized by XRD, FTIR and TGA. Dimethyl Acetamide/Lithium Chloride (DMAc/LiCl) solvent system was used for dispersing cellulose and clay. Results show that the preparation of OMMT was very successful; the X-ray diffraction results revealed that the interlayer spacing (2.17nm) for OMMT was increased compared with that (1.24nm) for Na-MMT. The composites exhibit higher thermal stability; addition of OMMT can considerably increase the decomposition temperature of cellulose matrix. An increase in thermal stability with clay content was observed by thermal analysis.